Nutrients and Organoleptic Properties of Soup and Stew made from Glossocalyx brevipes (Benth) - GTO, Otitoju; O, Otitoju; JU, Nwamara; AG, Kalu – Uka (Journal of Home Economics Research, 2024)
Proximate composition, nutrient composition and sensory evaluation of soup and stew made from Glossocalyx brevipes (Benth) were investigated. The proximate analysis showed that the moisture contents of the soup and stew ranged from 6.25 – 7.52%, protein 18.03 – 21.65%, fat 13.04 – 19.23%, crude fibre 6.12 – 7.58%, ash 6.10 – 6.89%, and carbohydrate 38.32 – 80.80% on wet weight basis. The result for the minerals and vitamin determination showed that the calcium content of the soup and stew samples ranged from (3.57 – 4.20mg/100g, iron (1.01 – 91.80mg/100g), magnesium (0.61 – 1.28mg/100g), sodium (0.30 – 0.33mg/100g), potassium (1.25 – 1.73mg/100g), manganese (1.01 – 92.13mg/100g), zinc (58.87 – 68.15mg/100g), copper(31.36 – 36.28mg/100g), pro -vitamin A (0.51 – 1.06mg/100g), niacin (0.38 – 0.49mg/100g), riboflavin (0.20 – 0.95mg/100g), pyridoxine (0.43 – 0.50mg/100g), cyanocobalamine (0.37 – 1.36mg/100g), vitamin E (2.82 – 3.30mg/100g) and vitamin C (2.91 – 3.53mg/100g).The results of the sensory evaluation indicated that G. brevipes stew leaf had the highest sensory attributes when compared to other products. In conclusion, the soup and stew made from G. brevipes leaf and bark contains nutrients, vitamin and mineral elements that are of high nutritional value. However, focusing our attention on underutilized vegetables is an effective way to help maintain a diverse and healthy diet and to combat micronutrient deficiencies and other dietary deficiencies particularly among the rural poor and the more vulnerable social groups.